FOCAL MECHANISM ANALYSIS OF VOLCANO-TECTONIC EARTHQUAKES IN SINABUNG VOLCANO IN OCTOBER 2010 ÃâÃâ DECEMBER 2011 PERIOD - HIDAYAT NIM: 12314061, ARY
Sinabung is a strato-type volcano located in Karo District, North Sumatera Province, Indonesia. Prior to the eruption of August 2010, Sinabung still considered as B-type volcano due to lack of activity since the year 1600. The eruption in August 2010 make it classified into type-A volcano. Since then, mount Sinabung’s activity has continued to fluctuate. As an effort to anticipate natural disasters that might occur, instrumental monitoring of volcanic activity is something that must be done. This study aims to determine the focal mechanism of Mount Sinabung to identify the tectonic settings in the area. The data used in this study are events occurred in the October 2010 – December 2011 period. The initial hypocenter location were determined using Geiger’s method. Furthermore, relocation was done to obtain a more accurate hypocenter location using the double-difference method. In this research, the identification of focal mechanism is done using moment tensor inversion method. The results of moment tensor inversion are dominated by the source mechanism in the form of sinistral strike slip. The mechanism were found in the eastern part of the main fault and the northwest-north part of Mount Sinabung. The source mechanism in the form of sinistral strike slip which were found in the research area may be associated with the main fault mapped on the surface and hidden fault that are not maped on the surface. In addition, normal faults also discovered within the area of Kawar Lake which indicate gravitational collapse around pre-existing caldera. In general, events occurred on Mount Sinabung and its surroundings in the study period were influenced by the pressure of magma that activated faults around Mount Sinabung.